Clerodendrum glandulosum Lindl.- An Important Wild Edible Plant by the Khasi Tribe of Meghalaya, India - Tynsong, H.; Dkhar, Melboreen (Indian Forester, 2025)
Clerodendrum glandulosum Lindl. (synonymous to Clerodendrum colebrookianum Walp.), often referred to as East Indian Glory Bower, is a perennial shrub that belongs to the Lamiaceae family. The plant has gained popularity among several tribes of North Eastern Region, India for the treatment of inflammatory, malaria, diabetes, indigestion, hypertension, fever, asthma, rheumatism, and other disorders and diseases. The present research aims to describe the distribution, propagation, and procedures involved in preparing leaves of C. glandulosum as vegetable by the Khasi tribe of Meghalaya. The study showed that C. glandulosum is a light dependent species. According to a household survey, agroforests are where the bulk of leaves are collected, with the rest coming from natural forests and home gardens. The plant’s leaves can be used to prepare a variety of dishes, the most popular of which include those prepared with dal (pulses), beef, and pork. This study revealed an important traditional knowledge system that if leaves harvested from plant for the first time the taste are bitter whereas, leaves harvested from plants on a regular basis each year are extremely testy. The plant thrives well on all kinds of landscape, even in those areas affected by coal mining in the state of Meghalaya.